Performance and difficulties in English language macro-skills by freshman students in selected colleges in Bacgiang City, Vietnam - Dimaano, Matilda Heralde; Hương, Ngô Thị Thu (Journal of English Language and Literature (ISSN: 2368-2132), 2019)
Knowledge in four macro-skills (i.e., listening, speaking, reading, and writing) are needed by learners for effective communication. The consistent search for improvement on these macro-skills helps promote self-development, effective communication and success in many different environments and context. Learners are motivated by opportunities that may come during learning of macro-skills which in turn allow the skills to subconsciously grow and develop naturally within the learner. This study aims to evaluate the performance and difficulties in English language macro-skills of freshmen Vietnamese students in selected Colleges in Bacgiang City. It made use of the descriptive method of research. The subjects of the study are 299 first year college students taking up basic English course in the three colleges in Bacgiang namely: Ngo Gia Tu College, Industry and Technology College and Vocational College. The data gathering instrument used is a teacher-made test. Results of the study showed that the level of students’ performance in the macro-skills of reading, writing, listening and speaking were all average. There were significant differences in the students’ performance among the macro-skills indicating non-relatedness of the macro-skills to each other. Students encountered difficulties in comprehension for macro-skills in reading and listening; while sharpening writing skill is the difficulty encountered for the macro-skill in writing; and pronunciation for the macro-skill in speaking. The most serious among the difficulties in macro-skills are those that pertain to comprehension both in reading and listening. The findings of the study suggest that English teachers have to be encouraged to provide more language exercises for their students to improve their language deficiencies; intervention measures must be developed based on the language deficiencies identified; similar studies on English language macro-skills will have to be conducted in universities to determine their students’ language performance and difficulties.